Corrupción y Arbitraje: A propósito de las Reglas IBA sobre conflictos de intereses - Ezcurra Rivero, Huáscar (2015)
In recent decades the arbitration has undergone extensive development in the Peru. However, this did not mean the absence of corruption in the arbitral proceedings. in this article the author points out some examples in which corruption manifests itself within them. Also, possible solutions are addressed with particular emphasis on competition, and its necessary condition: information. On this last, the iBA rules acquire special relevance for the resolution of conflicts of interest.